Effect Of Product Quality & Online Customer Review On Product E- Commerce Purchase Intention Among The Youths In Macassar City - Diah Ismayanti; Rosmiati, Ady Kurnia (STIE AMKOP, 2023)
This study aims to determine the effect of product quality & online customer review on product e- commerce purchase intention among the youths in macassar city is a qualitative study using sem pls.4 to test the hypothesis. The research population is young people who are students and students in the city of makassar, which is known for its highly consumptive society. The research sample was 100 people with 14 variable indicators, sampling using purposive sampling by distributing questionnaires using google form. The results showed that product quality has a significant effect on purchase intention and online customer review has a significant effect on purchase intention